Pengaruh pemberian jus buah dan yoghurt sari nanas terhadap kadar kolesterol pada penderita pra lansia hiperkolesterolemia - Zy Khairunnisa; Tonny Cortis Maigoda; Tetes Wahyu Witradharma (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Red guava, dragon fruit, and pineapple contain fiber and bioactive compounds that help lower cholesterol. Yoghurt with lactic acid bacteria also contributes to lowering cholesterol levels through biological mechanisms.Objectives: To assess the impact of fruit juice and pineapple yoghurt on reducing cholesterol levels in hypercholesterolemic pre-elderly patients.Methods: This pre-experimental study used a Randomized Block Design (RAK), dividing 30 participants into three groups: P0 (control), P1 (nutrition education and fruit juice), and P2 (nutrition education and pineapple yoghurt). The intervention lasted seven days, and cholesterol levels were measured before and after the intervention. Statistical analysis was conducted using the Kruskal-Walli’s test.Results: Participants were predominantly aged 51-59 years (60%), female (86,7%), and had high school education (86,7%). Pre-intervention cholesterol levels averaged 235 mg/dl (P0), 247 mg/dl (P1), and 253 mg/dl (P2). Post-intervention levels were 229 mg/dl (P0), 221 mg/dl (P1), and 224 mg/dl (P2). The Kruskal-Walli’s test showed no significant difference in cholesterol levels between the groups (pre p = 0,325, post p = 0,855).Conclusion: While cholesterol levels decreased slightly in all groups, the intervention showed no statistically significant effect.